Ukrainian Gendermuseum: Innovations in gender education in times of war and beyond - Isaieva, Tetiana; Clover, Darlene E. (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
This field note shares the work of Gendermuseum (Museum of Women's and Gender History), the only interactive non-governmental museum in Ukraine and post-soviet Eastern Europe. We trace its antecedents and feminist adult education aims, and practices. Framed through the lens of feminist adult education, we discuss how we use exhibitions and objects as creative learning tools and spaces. In particular, we focus on an exhibition titled HerStory and the War and how this gives visibility to the different/additional impact of war on women and equally importantly, women’s critical albeit often overlooked contributions to war efforts.